Post Operative Cognitive Dysfunction: A Literature Review - Irfan Ferdinand Tambunan (Open Access Indonesian Journal of Medical Reviews, 2021)
Along with ages, elderly patients with comorbid who undergoing surgical procedures are more likely to experience cognitive disorders such as decreased quality of life and loss of independence. This is known as postoperative cognitive dysfunction. The percentage is quite significant for old age to experience cognitive disorders. Ages, education level, health and mental status can be a factor causing cognitive disorders. Comprehensive assessment of objective mental, social and functional status can increase patient preoperative. Perioperative pharmacological management can reduce the incidence of POCD. For example, minimal use of propofol in spinal anesthesia may reduce POCD in hip fracture surgery. The use of dexmedetomidine in ventilated patients in the ICU may also reduce POCD. The etiology is still unclear, but there is a suspicion that the use of neurotoxic anesthetics can trigger the occurrence of POCD, but this has not been further proven.